2014
DOI: 10.1210/jc.2013-4129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pituitary Dysfunction After Severe Traumatic Brain Injury in Children and Adolescents: A Large Prospective Study

Abstract: At 1 year after the severe TBI, pituitary dysfunction was found in 8% of our study sample. We recommend systematic hormonal assessment in children and adolescents 12 months after a severe TBI and prolonged clinical endocrine follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 39 publications
2
52
1
Order By: Relevance
“…Poomthavorn et al 22 evaluated patients a long time after TBI and included 20 pubertal patients who had not experienced delayed or arrested puberty following TBI. Precocious puberty was described by Kaulfers et al 24 in three patients, but most of the cohorts included one case of precocious puberty in each studied group 20 22 29. Khadr et al 26 and Casano-Sancho et al 28 did not report a single case of precocious puberty.…”
Section: Search Strategymentioning
confidence: 95%
See 3 more Smart Citations
“…Poomthavorn et al 22 evaluated patients a long time after TBI and included 20 pubertal patients who had not experienced delayed or arrested puberty following TBI. Precocious puberty was described by Kaulfers et al 24 in three patients, but most of the cohorts included one case of precocious puberty in each studied group 20 22 29. Khadr et al 26 and Casano-Sancho et al 28 did not report a single case of precocious puberty.…”
Section: Search Strategymentioning
confidence: 95%
“…Other retrospective studies, such as the one published by Eunadi,20 restricted the dynamic tests to patients with low growth velocity; Norwood et al 25 and Khadr et al 26 carried out cross-sectional studies, showing a wide range of hypopituitarism from 48% to 25%. Prospective studies such as those by Kaulfers et al ,24 Niederland et al ,21 Casano-Sancho et al 28 and Personnier et al 29 used functional hormonal testing irrespective of clinical symptoms and found a high prevalence of pituitary dysfunction.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A study of 23 patients in the transition period (ages 16 to 25 years) found that hypopituitarism was present in 34.6% at 3 months after TBI, and at 12 months, hypopituitarism was present in 30.3% (13). On the other hand, the prevalence of hypopituitarism was only 8% in a study of 87 children and adolescents who were evaluated at 12 months after severe TBI (14), whereas in another study of 198 children with remote history of TBI in early childhood, low peak stimulated GH and cortisol levels were found in only 8% of the subjects (15).…”
Section: Epidemiologymentioning
confidence: 99%